The Effect of Financial Literacy on Millennial Generation's Investment Decisions in BRIS Stocks - Rendi Shafira, Dhafa; Puspitasari, Intan; Galih Prasaja, Mahendra (BALANCE: Economic, Business, Management and Accounting Journal, 2025)
Currently, the modernization era has changed human life and work. One of the things that is presently being considered is the level of financial literacy. One of the financial literacy in a person's investment decision. The purpose of this study is to examine the influence of financial literacy on the investment decisions of the millennial generation in BRIS stocks. This research is quantitative. The primary data used was taken from questionnaires given to respondents. Data testing is carried out by validity, reliability, and significance test testing (multiple linear). The results of the study showed that the level of financial literacy using the variable indicators of financial knowledge, financial attitudes, and financial behavior had a combined effect of 64% on investment decisions. Meanwhile, the remaining 36.0% of individual investment decisions are influenced by other variables that are not explained in this study